Exploring Source of Self-efficacy of Informatics and Computer Engineering Teacher Education Students during their Teaching Practicum - Sari, Rus Indah; Krismiyati, Krismiyati (International Journal of Active Learning, 2021)
Self-efficacy is one of the important aspects for teacher education students. High self-efficacy helps them to be more confident in doing their teaching practices. This can also affect their future performance as pre-service teachers, especially in the ICT field. In order to understand their self-efficacy, it is necessary to explore the source of self-efficacy thoroughly. This study aims to explore the sources of self-efficacy of ICT teacher -education students of Information and Computer Engineering Education at a private university in Salatiga who have completed their teaching practicum program. This study employs qualitative methods, and uses interviews for data collection. This involves 10 student teachers as participants. The results of the study describe the sources of self-efficacy of the student teachers. It identifies four sources of self-efficacy, they are mastery experience, vicarious experience, verbal persuasion and emotional arousal. The results show that the four main sources studied in this study contributed a lot in increasing the self-efficacy of the ICT student teachers.Â  Finally, this study offers recommendations for further research.